If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(u + -6) = 28 Reorder the terms: 7(-6 + u) = 28 (-6 * 7 + u * 7) = 28 (-42 + 7u) = 28 Solving -42 + 7u = 28 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 7u = 28 + 42 Combine like terms: -42 + 42 = 0 0 + 7u = 28 + 42 7u = 28 + 42 Combine like terms: 28 + 42 = 70 7u = 70 Divide each side by '7'. u = 10 Simplifying u = 10
| log(2)(7x+2)-5=0 | | 5x+9=3x+59 | | -778+x=-9987 | | E/o14/7=/10 | | 3x+18=2(x+15) | | y-49=x^2+14x | | 20+4u=92 | | 2(a-5)+6a=-6(a-5)+2 | | 5.6x=3.2x+13.2x | | 20=t+19 | | (2x-1)*x-16=0 | | X*(x-1)+(x-2)=100 | | 3x+7=2(x+7) | | 39=2y+17 | | 7000+x=9983 | | -2(-4+4m)=8-2m | | xsqured-49=0 | | 48=8z | | 9x^2-9y^2+9x+6y=0 | | x^2+8x=9+y | | -4y+12=-8 | | 22x+2(3x+5)=65 | | x^2=-2y | | y+x=x^2+1 | | 4(x-2)-10x=-2(3x+4) | | 34a+37=7+36a | | x+66=198 | | 3x^2+5x+3y^2+4y+7=0 | | (m+1)x^2+mx+5=0 | | (5x+32)= | | 3(2x+9)=93 | | (6x-3+8)=(3x+10-x) |